Preference of Social Network Sites for Uncertainty Reduction among International Students - Gambo, Sarah (Doğu Akdeniz Üniversitesi, 2020)
International students are distant from their homes and seek for an appropriate platform which they can relate with home, North Cyprus and others. This research considers the preference of Social Networking Sites (SNS), particularly Facebook and Instagram by the international tertiary students. The various strategies employed by the students when they would like to reduce their levels of uncertainty have been also considered. 499 international students who study at the Eastern Mediterranean University participated in the study. The study made use of quantitative methodology and administered questionnaire as a means of data collection, in order to ascertain students’ preference of SNS. Findings revealed that although Facebook seems to be the most popular, Instagram seems to be significant in communicating with people in North Cyprus, and others than the use of Facebook. Also, the three uncertainty reduction strategies (URS) passive, active and interactive strategies have positive influence when SNS was used in inferential statistics to ascertain the influence when use as the mediating variable. Students are active in the selection of their media to reduce their uncertainty thus; they have positive relationship. The two theories used (Uses and Gratification and Uncertainty Reduction Theories) affirmed that youth are selective and active when selecting a medium for communication thus their suitability for the research. Keywords: Preference, Social Networking Sites (SNSs), Uncertainty Reduction Theory, International students, Eastern Mediterranean University.

ÖZ:Uluslararası öğrenciler evlerinden uzakta olmalarından dolayı kendilerine evleri, Kuzey Kıbrıs ve diğerleriyle ilişki kurabilecekleri uygun bir platform aramaktadırlar. Bu araştırma uluslararasi üniversitesi öğrencilerin, Sosyal Ağ Sitelerinin, özellikle Facebook ve Instagram'ın tercihlerini dikkate almaktadır. Öğrencilerin belirsizlik seviyelerini azaltmak istediklerinde kullandıkları çeşitli stratejileri de dikkate almaktadır. Bu çalışmaya, Doğu Akdeniz Üniversitesi’ndeki eğitimgören 449 uluslararası öğrenci katılmıştır. Çalışmada nicel metodoloji kullanılmıştır ve veri toplama aracı olarak öğrencilerin sosyal medya tercihlerini belirlemek için anket tercih edilmiştir. Bulgular, Facebook en popüler sosyal medya platformu gibi görünse de Instagram'ın Kuzey Kıbrıs ve diğerleriyle iletişim kurmada Facebook'un kullanımından daha önemli olduğunu göstermektedir. Ayrıca, üç belirsizlik azaltma stratejisi, aktif, pasif ve etkileşimli stratejiler, Sosyal Ağ Sitelerinin kullanıldiğinda olumlu etkiye sahip tir. Öğrenciler belirsizliklerini azaltmak için medyalarının seçiminde aktiftirler, bu nedenle pozitif bir ilişkiye sahiptirler. Kullanılan iki teori (Kullanımlar ve Doyumlar ve Belirsizliği Azaltma Teorileri) kullanım sırasında uygulamalarını ve araştırma için nasıl kullanıldığını teyit etmiştir. Anahtar Kelimeler: Tercih, Sosyal Ağ Siteleri (SNS), Belirsizliği Azaltma Teorisi, Uluslararası öğrenciler, Doğu Akdeniz Üniversitesi.
Doctor of Philosophy in Communication and Media Studies. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Communication And Media Studies, 2020. Supervisor: Prof. Dr. Bahire Efe Özad.
Keywords: Students-International Students-Social Media-Social Networking Sites-Eastern Mediterranean University-Cyprus (Turkish Republic of Northern Cyprus, 1983-); Education, Higher-Universities-Students-Social Media-Social Networking Sites-Facebook-Instagram; Preference; Social Networking Sites (SNSs); Uncertainty Reduction Theory; International students; Eastern Mediterranean University